UTILIZAÇÃO DA TÉCNICA DE DRENAGEM LINFÁTICA MANUAL NO PÓS-OPERATÓRIO DE LIPOASPIRAÇÃO - Alves, Bruna R. B.; Schock, Jéssica W.; Scherf, Gabriela; Gerhardt, Letiane G. (Salão do Conhecimento, 2013)
Resumo